Effect of ELVAX polymer subgingival implants with echistatin on extracted and reimplanted rats’ teeth - Pinheiro, Bethânia Camargo; Pinheiro, Tiago Novaes; Leite, Milena Gomes Melo; Garcia, Roberto Brandão; Bernardineli, Norberti; Faria, Flávio Duarte [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Bramante, Clovis Monteiro (Springer Nature, 2023)
To investigate the effect of ELVAX polymer subgingival implants incorporated with echistatin peptide on incisor reimplanted tooth in rats. Forty-two male Wistars rats were divided into two groups: echistatin-treated rats (E) and control rats (C). The animals had their right maxillary incisors extracted and treated according to the International Association of Dental Traumatology replantation protocol. The extra-alveolar dry period was 30 and 60 min, and the post-surgical experimental periods were 15, 60, and 90 days. The samples were stained with H&E and analyzed for the presence of an inflammatory response, incidence of resorptions, and dental ankylosis. Results were statistically analyzed (p < 0.05). The presence of inflammatory resorption was significantly higher in group C at 30 and 60 min extra-alveolar time, in the 15-day postoperative period as compared with the E group (p < 0.05). Dental ankylosis was significantly more prevalent in group E in 30 min extra-alveolar time and 15 days postoperative period (p < 0.05). However, in 60 min extra-alveolar time and 60 days postoperative period, dental ankylosis was more prevalent in C group (p < 0.05). The use of ELVAX subgingival implants with echistatin demonstrated therapeutic potential in preventing the experimental resorption process after replantation of maxillary incisors in rats.
Keywords: Echistatin; Root resorption; Tooth avulsion